Rozwiąż nierówność:
b) 2x + 3 < 3
d) 2x + 5 < 3x + 11
f) 2x + 5 - x ≤ x + 11
h) 5x - 11 > 3x + 9
j) x - 17 > -2x - 17
l) 2x + 5 ≤ 3x + 10

Rozwiąż nierówność:
a) 4 > 5(x + 1)
c) 3(x + 2) - 2(3 - x) ≥ 8
e) 5(2x + 3) ≤ 2(x + 6) + 15
g) 7(x-1) - 3(2x + 3) ≤ 2(x + 2) - 22

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-13T10:45:50+01:00
Rozwiąż nierówność:
b) 2x + 3 < 3
2x<3-3
2x<0
x<0
d) 2x + 5 < 3x + 11
2x-3x<11-5
-x<6 /*(-1)
x>-6

f) 2x + 5 - x ≤ x + 11
x-x+5 ≤11
5≤11
sprzecznosć

h) 5x - 11 > 3x + 9
5x-3x > 9+11
2x > 20
x > 10

j) x - 17 > -2x - 17
x+2x>-17+17
3x>0
x>0

l) 2x + 5 ≤ 3x + 10
2x-3x ≤ 10-5
-x ≤ 5 /*(-1)
x ≥ -5


Rozwiąż nierówność:
a) 4 > 5(x + 1)
4> 5x+5
4-5 >5x
5x <-1
x< -1/5

c) 3(x + 2) - 2(3 - x) ≥ 8
3x+6-6+2x ≥ 8
5x ≥ 8
x ≥ 8/5
x≥ 1 3/5

e) 5(2x + 3) ≤ 2(x + 6) + 15
10x +15 ≤ 2x+12+15
10x-2x ≤ 27-15
8x ≤ 12
x ≤ 12/8
x≤ 1 1/2

g) 7(x-1) - 3(2x + 3) ≤ 2(x + 2) - 22
7x-7 -6x-9 ≤2x+4-22
x-2x ≤-18+16
-x ≤-2 /*(-1)
x≥ 2
2 5 2